2021
DOI: 10.1186/s13561-021-00332-0
|View full text |Cite
|
Sign up to set email alerts
|

The addition of neoadjuvant pertuzumab for the treatment of HER2+ breast cancer: a cost estimate with real-world data

Abstract: Background Breast cancer (BC) is largely prevalent worldwide. HER2-positive BC account for roughly 20–25% of all BC cases and has an overall survival lower than other BC. Innovation on BC therapeutics is a constant, but novel therapies have higher costs. Therefore, cost-effectiveness research is essential to provide healthcare decision-makers with solid foundations for a resource allocation. This study aims to estimate the average direct medical costs/patient and cost-effectiveness of adding pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 15 publications
2
7
0
Order By: Relevance
“…Although pertuzumab as neoadjuvant therapy is not really a novelty, the evidence of its value and cost is still limited. Our findings were in line with those reported in previous published studies [ 20 , 45 , 46 ]. Borges and colleagues found that the addition of pertuzumab as neoadjuvant therapy was associated with an increase of 40% of the overall costs per patient and an improvement of clinical outcomes (i.e., pCR response) [ 45 ].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Although pertuzumab as neoadjuvant therapy is not really a novelty, the evidence of its value and cost is still limited. Our findings were in line with those reported in previous published studies [ 20 , 45 , 46 ]. Borges and colleagues found that the addition of pertuzumab as neoadjuvant therapy was associated with an increase of 40% of the overall costs per patient and an improvement of clinical outcomes (i.e., pCR response) [ 45 ].…”
Section: Discussionsupporting
confidence: 94%
“…Our findings were in line with those reported in previous published studies [ 20 , 45 , 46 ]. Borges and colleagues found that the addition of pertuzumab as neoadjuvant therapy was associated with an increase of 40% of the overall costs per patient and an improvement of clinical outcomes (i.e., pCR response) [ 45 ]. However, it should be noted that this was a real-world study including a small cohort of patients.…”
Section: Discussionsupporting
confidence: 94%
“…This can be burdensome and may lead to dehydration, electrolyte imbalances and sometimes hospitalization [ 1 , 24 ]. In addition, the costs of pertuzumab increase health care expenses [ 25 ]. Therefore, a high need remains to select patient in whom pertuzumab can be omitted.…”
Section: Discussionmentioning
confidence: 99%
“…This study follows two consecutive retrospective cohorts of women with HER2-positive breast cancer (≥ 18 years old) who received NeoT between January 2012 and June 2017 in the Breast Clinic of IPO-Porto. [ 23 ] This is a public hospital in the north of Portugal, integrated in the Porto Comprehensive Cancer Centre, specialized in the treatment and management of cancer. The Breast Clinic at IPO-Porto treated 1243 cases in 2017, making it the largest breast cancer treatment center in Portugal and one of the most relevant in Europe.…”
Section: Methodsmentioning
confidence: 99%